2019 IEEE International Conference on Systems, Man and Cybernetics (SMC) 2019
DOI: 10.1109/smc.2019.8914418
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Volume Coverage of Robot Workspace using On-Robot Time-of-Flight Sensor Arrays for Safe Human Robot Interaction

Abstract: In this paper, an analysis of the sensing volume coverage of robot workspace as well as the shared humanrobot collaborative workspace for various configurations of onrobot Time-of-Flight (ToF) sensor array rings is presented. A methodology for volumetry using octrees to quantify the detection/sensing volume of the sensors is proposed. The change in sensing volume coverage by increasing the number of sensors per ToF sensor array ring and also increasing the number of rings mounted on robot link is also studied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…They showed that with their approach it is possible to increase the overall production efficiency. Kumar et al researched on how to calculate the amount of sensors needed for a specific area as well as how SSM can be achieved from the surface of the robot [11,12]. Grushko et al proposed the approach of giving haptic feedback to the operator through vibration on the operator's work gloves [13].…”
Section: Introductionmentioning
confidence: 99%
“…They showed that with their approach it is possible to increase the overall production efficiency. Kumar et al researched on how to calculate the amount of sensors needed for a specific area as well as how SSM can be achieved from the surface of the robot [11,12]. Grushko et al proposed the approach of giving haptic feedback to the operator through vibration on the operator's work gloves [13].…”
Section: Introductionmentioning
confidence: 99%